Digital Marketing Assistance Through Google Maps Application in an Effort to Improve UMKM Development in Jayamulya Village, Kroya District, Indramayu Regency - Putri Rahmah; Ati Agustin C; Yosi Nopiyanti (Kawakib: Journal of Multidisciplinary Research, 2025)
Jayamulya Village, located in Kroya District, Indramayu Regency, is a village with lower-middle economic potential, dominated by the agricultural sector, especially rice. However, Jayamulya Village still faces significant challenges in terms of human resource development, especially related to digital management capabilities, which are very important in the current era of globalization and digitalization. One sector that is greatly affected by these limitations is the Micro, Small, and Medium Enterprises (UMKM) sector, which has not had a significant economic impact in this village. The support program that is being held aims to overcome the economic problems faced by UMKM actors in Jayamulya Village. This program focuses on efforts to increase the capacity of UMKM actors who are still not optimal in marketing their products. One of the solutions offered is effective digital management, including the use of Google Maps to register their businesses. Through this registration, UMKM can include detailed information such as operating hours, telephone numbers, addresses, and business descriptions, which will certainly help potential customers in getting relevant and complete information. In addition, this program also aims to provide education to UMKM about the importance of marketing through digital platforms, so that they can reach a wider target consumer. Data for this program was obtained through survey methods, interviews, and direct observation of business actors in the village, which were then analyzed using qualitative and quantitative approaches. This approach involves training and guidance related to market segmentation, marketing strategies, and the importance of digital presence for UMKM, especially through registration on Google Maps. The results of this program are expected to help UMKM in Jayamulya Village to increase their sales and, ultimately, contribute to improving the village economy as a whole. In addition, this program also provides a direct approach to evaluate whether there are significant changes in business actors after the implementation of the program, so that the objectives of this service can be achieved properly and provide sustainable benefits for the Jayamulya Village community.